Constraints as faced by the cauliflower growers in use of recommended cauliflower production technology - Ghaswa, Ramdhan; Sharma, N.K.; Kumari, Sunita; Bana, S.K. (Annals of Agricultural Research, 2016)
Cauliflower (Brassica oleracea var. botrytis) is one the most important as well as popular winter vegetable crops, which is grown through out the country. Vegetables play an important role in the maintenance of human health. These make diet nutritive and balanced. A balanced diet requires a proper quota of fresh vegetables. About 300 gm of vegetables are needed (90 gm root vegetables, 120 gm green vegetables and 90 gm other vegetables). But, about 220.8 gm vegetables per day per capita are available (Indian Agriculture, 2011). The present study was conducted in Jaipur district of Rajasthan which was selected purposely. The Jaipur district consists of 13 panchayat samities, Out of which two panchayat samities namely Bassi and Amber were selected on the basis of the highest area and production. In all 12 villages were selected from the selected gram panchayats by using simple random sampling technique and a sample of 84 cauliflower growers was selected from these villages by using proportionate random sampling technique. The ’’financial constraints’’ and "marketing constraints" were most perceived by the cauliflower growers followed by "technical constraints". Whereas the "input constraints" were perceived least by the cauliflower growers.